Tackling Non-communicable Diseases in Asia Countries Systematic Review - Ernita, M; Wibowo, A (KnE Life Sciences, 2019)
NCDs impact the lives and health of many people, effective policies and program have to be put in tackling NCDs. This study aimed to find out the program and policies in asia countries. The method was a systematic review by using the search facility database online through uindonesia summon serials solutions and Proquest by year of publication from 2007 to 2016. Journals were screened by tittle and abstract according to research topic, then selected using inclusion and exclusion criterias and at the end we found 8 journals to review. The epidemic of NCDs influence the universal health coverage in some countries. The ongoing program in tackling NCDs in southeast asia countries are a community-based approach, improve the skill of health workers, increase an investment in public health intervention programs and involve all health sectors and related stakeholders. The policy maker should make the program that focus on health promotion, strengthening infrastructure including human resources and early diagnosis on diseases. Keywords: tackling, non communicable diseases, policies, program